The rise, the fall, and the recovery of Southeast Asia's minidragons :bhow can their history be lessons we shall learn during the twenty-first century and beyond? - Hollingsworth, David Anthony d 1970- (Lexington Books, 2007)
This book explores how a clear-eyed set of policies can govern a country's wellbeing from an economic standpoint and the vision it takes to propel a country to new heights. The author considers not just development, but how development was undone by policies and actions that were not governed by a consistent long-range vision